Prevalence of low bone mineral density in Human Immunodeficiency Virus-infected patients and its correlation with other determinants - Mahajan, Swati; Raina, Rajiv; Jhobta, Anupam (Eastern Journal of Medical Sciences, 2021)
Background: The patients infected with human immunodeficiency virus (HIV) are potentially at risk of low bone mineral density (BMD). The present study was done to find out the prevalence of low BMD in HIV-infected patients and its correlation with other factors such as gender, body mass index (BMI), CD4 count, and highly active antiretroviral therapy (HAART). Methods: This was an observational cross-sectional study conducted in a tertiary care center for 1 year period. A total of 127 HIV-infected patients were evaluated for BMD by dual-energy X-ray absorptiometry (DEXA) scans at two sites lumbosacral spine and bilateral neck femur. Correlation with other factors was also studied. Results: The diagnosis of low BMD was established in 105 (82.67%) patients. Osteoporosis (44.1%) was more common than osteopenia (38.6%) at the lumbosacral spine. The mean T score of the DEXA lumbar spine and bilateral neck femur was observed to be ?2.113 and ?1.379, respectively. Males (88.73%) had low BMD than females (75%). Approximately 94.5% of subjects having BMI 18. After treatment, 47 patients had CD4 count 400. Forty-three patients out of 47 (91.5%) had low BMD and 62 out of 80 (77.5%) had low BMD. Conclusion: Low BMD is prevalent in HIV-infected subjects. Low BMI, persistently low CD4 count, tenofovir containing HAART regimen showed a positive correlation with low BMD. Hence, HIV infection should be considered as a risk factor for bone disease.